Pengaruh Profitabilitas, Leverage, Capital Intensity Dan Ukuran Perusahaan Terhadap Tax Avoidance - Helmi, Syarif M; Kurniadi, Ahmad; Faisal, Ahmad; Domineka, Billy Ghozali (Universitas Bina Sarana Informatika, 2025)
This study aims to analyze the effect of profitability, leverage, capital intensity, and firm size on tax avoidance. Tax avoidance is a corporate strategy to minimize tax burdens, which can impact a company's financial policies. The objective of this research is to determine how tax avoidance is influenced by profitability, leverage, capital intensity, and firm size. The population of this study consists of financial reports of mining companies listed on the Indonesia Stock Exchange between 2019 and 2022. Using a purposive sampling method, 96 observational data points that met the testing requirements were selected. The data analysis techniques employed in this study include descriptive statistical analysis, multiple linear regression, classical assumption tests, t-tests, F-tests, as well as the coefficient of determination test, with data processing conducted using SPSS 26. The results of this study indicate that tax avoidance is significantly influenced by profitability and leverage, whereas capital intensity and firm size do not have a significant effect. These findings provide valuable insights for the government, society, and corporate management to better understand the factors affecting tax avoidance practices